Reaction temperature dependent shape-controlled studies of copper-oxide nanocrystals. (22nd June 2018) - Shah, Janki; Ranjan, Mukesh; Gupta, Sanjeev K; Satyaprasad, A; Chaki, Sunil; Sonvane, Yogesh
Abstract: In the developing era, metal oxide nanomaterials are intensively pursued due to their prominence applications in different applied and technological fields. The transition metal oxide, copper oxide is a dominant candidate for magnetic storage devices, sensor, and solar energy transfer as a heat absorber, super capacitors and mainly as a good catalyst in chemical reactions. Here, CuO nanostructures with different shapes (nanoparticle, cubelike, rectangular, nanobar and nanorod) are synthesized by precipitation method from CuCl2 precursors. The CuO all structures are characterized by X-ray diffraction for the structural study. CuO different shapes morphological phenomena are carried out from SEM and TEM. The thermal properties are calculated by recording thermo-curves, viz. thermogravimetric (TG), differential thermogravimetric (DTG). Thermogravimetric analysis revealed CuO all structures show weight loss at 340 K to 380 K and 1000 K to 1250 K region because of water evaporation and combustion of organic compounds respectively. Activation energy, Arrhenius factor, activation enthalpy, activation entropy and Gibbs free energy for the decomposition of CuO were determined using the Coats-Redfern (CR) method for all shaped structures.